What happens to plant mitochondria under low oxygen? An omics review of the responses to low oxygen and reoxygenation. (11th May 2014) - SHINGAKI‐WELLS, RACHEL; MILLAR, A. HARVEY; WHELAN, JAMES; NARSAI, REENA
Abstract Floods can rapidly submerge plants, limiting oxygen to the extent that oxidative phosphorylation no longer generates adequate ATP supplies. Low‐oxygen tolerant plants, such as rice, are able to adequately respond to low oxygen by successfully remodelling primary and mitochondrial metabolism to partially counteract the energy crisis that ensues. In this review, we discuss how plants respond to low‐oxygen stress at the transcriptomic, proteomic, metabolomic and enzyme activity levels, particularly focusing on mitochondria and interacting pathways. The role of reactive oxygen species and nitrite as an alternative electron acceptor as well as their links to respiratory chain components is discussed. By making intra‐kingdom as well as cross‐kingdom comparisons, conserved mechanisms of anoxia tolerance are highlighted as well as tolerance mechanisms that are specific to anoxia‐tolerant rice during germination and in coleoptiles. We discuss reoxygenation as an often overlooked, yet essential stage of this environmental stress and consider the possibility that changes occurring during low oxygen may also provide benefits upon re‐aeration. Finally, we consider what it takes to be low‐oxygen tolerant and argue that alternative mechanisms of ATP production, glucose signalling, starch/sucrose signalling as well as reverse metabolism of fermentation end products promote the survival of rice after this debilitating stress.